(untitled) (Педагогіка вищої та середньої школи, 2002)
The article deals with the questions of forming of vocal skills in the process of teaching pupils to sing: timbre qualities of voice, breathing, registries, attack of the sound, process of voice-making. The article is addressed to the pedagogical universities teachers on vocal music.